ICT enabled education: ethical and axiological competence formation - Frolova, Tatiana N.; Umarova, Zara Ya.; Suhorukhih, Alexey V.; Lazareva, Yuliya B. (Opción, 2020)
Today, information and education technologies are actively used in education. However, more attention is paid to the formation of practical rather than ethical and axiological skills. In this regard, the objectives of the study have been defined: to conduct a survey among the teachers of Russian universities to determine their socio-ethical ICT literacy; to conclude whether teachers are able to form ethical competences in students when implementing ICTs in their classrooms. According to the survey results, the teachers have a high level of ethical literacy, but they do not fully understand the importance of developing such skills when using ICTs.